Application of Webqual 4.0 and Importance Performance Analysis Methods in Analyzing The Quality of Information Technology SIPENDEKAR Services - Kartika, Rina; Syahrullah, Syahrullah; Rasmita, Hajra; Rinianty, Rinianty; Yanti, Wirda; Lapatta, Nouval Trezandy (CCIT (Creative Communication and Innovative Technology) Journal, 2025)
Information technology plays a very important role, especially in the field of education, one of which is through the use of websites. The Department of Information Engineering at Tadulako University is one of the universities that utilizes websites, one of which is the information system for administrative services and final assignments (SIPENDEKAR). Sipendekara is designed to facilitate the submission of titles, guidance, and proposal exams, final exams, and thesis exams. But so far, there has been no research that measures the quality of the sipendekar website based on perceptions of usability, information quality, and service interaction quality using the IPA method. This study aims to determine the quality of Sipendekar services using the webqual 4.0 method as the basis for determining the questionnaire. Then the Importance Performance Analysis method to analyze questionnaire data to identify attributes that have met and have not met user expectations. The results showed an average level of conformity of 92.63%. The average gap analysis result is -0.33. The results of the Cartesian quadrant there are 4 attributes in the first quadrant that are prioritized for improvement and there are 9 attributes that achieve a high level of satisfaction and only need to maintain quality.